Effect of duration of pre-operative admission on surgical site infection in major abdominal surgeries: an observational study - Gupta, Alka Shantiprakash; Shetty, Arthika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Surgical site infection (SSI) are second most common cause of mortality in surgical patient, situation has been further complicated by emergence of drug resistant strains. The importance of preventing surgical site infections is well recognized since they lead to increased morbidity, prolonged hospital stays, need for readmission, high end antibiotic treatment and re-surgery. The study was done to see if incidence of SSI is decreased with decreased pre-operative admission time. Others factors associated with SSI were analysed including the microbiological spectrum. Methods: The study was an analytical, observational, case control study. Sixty (60) cases each of gynaecology and obstetrical post-operative patients who developed SSI within 30 days were taken as cases and who did not develop SSI were taken as controls and preoperative admission time was analysed in both cases and controls to observe if risk of surgical site infections decreases due to decreased exposure to nosocomial pathogens when the pre-operative admission time was less than 48 hours. Results: Author found that there was statistically significant difference in the time between surgery and admission in the gynaecological surgeries with p value 0.023, as compared to the obstetrics surgeries where there was no statistically significant difference. Common organism isolated was E. coli sensitive to gentamicin. Conclusions: From this study, it seems to be a good policy to evaluate the patient on OPD basis and admit them about 24 to 48 hours prior to the surgery rather them keeping them admitted for prolonged duration in wards for diagnostic evaluation. This prevents nosocomial contamination in the patient’s skin flora thereby preventing SSI. This practice not only conserves the hospital resources but also makes the patient turn over faster. Further this might in the long run reduce the antibiotic resistant hospital flora.